A bovine viral diarrhea virus type 1a strain in China: isolation, identification, and experimental infection in calves - Wang, Wei (BioMed Central, 2014)
BACKGROUND: Bovine viral diarrhea virus (BVDV) is one of the most important pathogens in cattle. Previously, BVDV sub-genotypes of 1b, 1c, 1d, and 1 m were detected in China. However, isolation of BVDV type 1a from cattle has not been reported in China. In 2010, twenty nasal swabs and blood samples were collected from the cattle suspected BVDV infection in Henan province, China. A BVDV isolate was isolated using cell culture, and the pathogenesis of the virus isolate was studied. METHODS: Virus isolation was performed on MDBK cells. The virus identification was conducted by RT-PCR, neutralization test and immunofluorescence assay. In order to determine the genotype of the newly isolated virus, the 5′ un-translated region (5′UTR) of the virus isolate was cloned, sequenced and phylogenetically analyzed. To evaluate the virulence of the virus isolate, four BVDV sero-negative calves were intranasally inoculated with the virus suspension. Rectal temperatures and clinical signs were recorded daily. Blood samples were analyzed for changes in white blood cell counts, and tissue samples were taken for histopathology analysis. RESULTS: A new isolate of bovine viral diarrhea virus (BVDV), named HN01, was isolated from the nasal swabs using MDBK cell culture. The HN01 strain caused cytopathic effect (CPE) in MDBK cell cultures after two passages. The virus specifically reacted to BVDV1-specific monoclonal antibody in an immunofluorescence assay. A fragment of 288 bp of genome from this isolate was amplified by the RT-PCR. Phylogenetic analysis of 5′UTR indicated that the virus was BVDV 1a. In the pathogenesis study, four calves experimentally infected with the BVDV strain developed depression, cough and other clinical signs. Calves showed high temperature over 40°C, and white blood cell counts dropped more than 40%. CONCLUSIONS: A new subgenotype 1a strain of BVDV was firstly isolated from dairy cattle in China. The experimental infection showed that the virus was moderate pathogenic to cattle and can be used as a BVDV challenge virus to evaluate the efficacy of BVDV vaccines in the target animals.